Indication guidelines for Mohs micrographic surgery in skin tumors - Selma Schuartz Cernea; Gabriel Gontijo; Eugenio Raul de Almeida Pimentel; Roberto Gomes Tarlé; Glaysson Tassara; Juliana Areas de Souza Lima Beltrame Ferreira; Victor Miguel Coutinho Fernandes; Wanderley Marques Bernardo (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Mohs micrographic surgery is a technique used to excise skin tumors based on comprehensive surgical mapping, in which the surgeon removes the tumor, followed by a complete histological evaluation of the tumor's margins. The correlation of the presence of a tumor in histological examinations and its precise location on the surgical map result in a complete removal of the tumor with maximum normal tissue preservation. The present article seeks to provide general practitioners and healthcare specialists with guidelines regarding recommendations for Mohs micrographic surgery to treat skin tumors, based on the most reliable evidence available in medical literature on the subject. This bibliographic review of scientific articles in this line of research was conducted based on data collected from MEDLINE/PubMed. The search strategy used in this study was based on structured questions in the Patient, Intervention, Control, and Outcome (PICO) format. MeSH terms were used as descriptors. The indications of this technique are related to recurrence, histology, size, definition of tumor margins, and location of tumors. These guidelines attempt to establish the indications of Mohs surgery for different types of skin tumors.